Serupa Tapi Tidak Bersama : Pemberitaan Media Dalam Konflik Pendirian Masjid Imam Ahmad Bin Hanbal di Kota Bogor - Afandi, Yusuf Afandi (KOMUNIDA : Media Komunikasi dan Dakwah, 2024)
ABSTRACT This study aims to analyze the framing of media coverage related to the conflict over establishing the Imam Ahmad Bin Hanbal Mosque in Bogor City. This conflict attracted public attention because it involved various parties, including the local community, government, and religious organizations. The framing analysis method used in this research is Robert Entman's model, which includes four elements: problem definition, problem cause, moral judgment, and problem-solving. Data was obtained from several national and local media outlets that were selected based on the intensity of coverage and diversity of perspectives. The analysis results show that the media have certain framing tendencies influenced by their respective agendas and ideologies. Some media tend to highlight social and religious tensions, while others emphasize legal aspects and government policies. In addition, the study found that media framing played an essential role in shaping public opinion and people's perceptions of the conflict. The study concludes that a deeper understanding of media framing techniques can help people criticize the information they receive and develop more objective thinking. This study also provides recommendations for the media to be more balanced and accurate in reporting sensitive religious and social diversity issues. Keywords : Framing analysis, media, mosque establishment conflict, Imam Ahmad Bin Hanbal Mosque, Bogor City